LNMAT1 Promotes Invasion-Metastasis Cascade in Malignant Melanoma by Epigenetically Suppressing CADM1 Expression - Mou, Kuanhou; Zhang, Xiang; Mu, Xin; Ge, Rui; Han, Dan; Zhou, Yan; Wang, Lijuan (Frontiers in Oncology, 2019)
The invasion-metastasis cascade is one of the most important factors relating to poor survival and prognosis of malignant melanoma (MM) patients. Long non-coding RNA lymph node metastasis associated transcript 1 (LNMAT1) is a key regulator in lymph node metastasis of multiple cancer types, but the roles and underlying mechanisms of LNMAT1 in the invasion-metastasis cascade of MM remain unclear. In the present study, we aimed to investigate the expression and function of LNMAT1 in MM. Here, we found that LNMAT1 was upregulated in MM tissues and cells, and its expression levels were further enhanced in MM patients with lymph node metastasis and metastatic MM cells. Using loss-of-function assays, we found that LNMAT1 promoted cell migration and invasion and lung metastasis in MM in vitro and in vivo. Moreover, we found that cell adhesion molecule 1 (CADM1), the established tumor suppressor in MM, was the downstream target of LNMAT1. Mechanistically, LNMAT1 epigenetically suppressed CADM1 expression by recruiting EZH2, the key regulator of trimethylation of histone H3 at lysine 27 (H3K27me3), to the CADM1 promoter, resulting in transcriptional inhibition of CADM1. Lastly, rescue assays demonstrated that LNMAT1 promoted cell migration and invasion of MM by suppressing CADM1 expression. Our findings elucidate a new mechanism for LNMAT1-mediated invasion-metastasis cascade in MM and suggest that LNMAT1 may be a new therapeutic target and prognostic predictor for MM.